A CONCEPTUAL ICOOKIES MULTI-SIDED BUSINESS MODEL: BUILD-UP SKILLS, ENHANCE JOB OPPORTUNITIES & ENTREPRENEURSHIP FOR B40 COMMUNITY IN GLOBAL COOKIES BUSINESS - Zin Ko Ko; ABDUL MUHAIMIN; MUHAMMAD ‘AFIF AKMAL; ABDUL RAHMAN AHMAD DAHLAN (Journal of Information Systems and Digital Technologies, 2022)
The purpose of this paper is to present a conceptual iCookies business model, with a digital platform and apps, that is aligned with the United Nations Sustainable Development Goals (SDG) in reducing poverty; building-up valuable skills, decent works and entrepreneurship including among the B40s; and in providing consumers with quality & variety cookies worldwide. The B40 community are struggling to find a stable and decent job, especially in this pandemic time. Job opportunity with a digital platform to start a business will benefit the low-income people and B40s. B40s pains include lack of funds and skills to start the business. As for sellers, the online marketplace will help them promote and market their products. The digital platform will help sellers gain more customers and make higher sales. A trusted platform will help donors make the donation and feel at ease without having to worry about scams or implicit donations. Donors will attract to make donations on the platform as it is trusted for the transparency of the donation process. The Customer Segments in this paper are organizations & individuals who want to buy their favourite cookies locally & globally; cookies sellers who want to promote their cookies; low-income people (B40), underemployed, and unemployed who want valuable and employable in baking cookies; and donors who want to build a philanthropic brand on creating employment and companies who want a new generation of employees to learn their cookies. This paper highlights the difficulties faced by various Customer segments along with the conceptual solution to overcome the difficulties. Poverty among B40s (SDG1 - No Poverty), hunger faced by the B40s (SDG2 - Zero Hunger) and unemployment challenges are among the obstacles or significant problems identified (SDG8 - Decent Work and Economic Growth). The key problems were identified, and suitable conceptual solutions were created using the Design Thinking (DT) technique. This process includes completing a literature review, testing, and questionnaires to identify and describe the issue of segments, as well as brainstorming, and testing potential solutions. The methodology adopted for this paper is based on the Design Thinking process using literature review, biz modelling tools namely Business Model Canvas (BMC) and Value Proposition Canvas (VPC), and survey. This paper intends to help the consumer to enjoy a variety of cookies around the world and help cookies sellers by providing an online platform. Moreover, the B40 people will gain skills and get job opportunities to make an income. Last but not least, the donors can make their donations without any worries.